2015
DOI: 10.7554/elife.08942
|View full text |Cite
|
Sign up to set email alerts
|

Resection is responsible for loss of transcription around a double-strand break in Saccharomyces cerevisiae

Abstract: Emerging evidence indicate that the mammalian checkpoint kinase ATM induces transcriptional silencing in cis to DNA double-strand breaks (DSBs) through a poorly understood mechanism. Here we show that in Saccharomyces cerevisiae a single DSB causes transcriptional inhibition of proximal genes independently of Tel1/ATM and Mec1/ATR. Since the DSB ends undergo nucleolytic degradation (resection) of their 5′-ending strands, we investigated the contribution of resection in this DSB-induced transcriptional inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…This conclusion highlights the differences between different biological systems since DDR kinases ATM and ATR are dispensable for transcriptional repression in yeast , while they play key roles in mammals, as described above. Several observations seem to exclude a key role for resection in DSB‐dependent transcriptional silencing in mammals.…”
Section: Dna‐end Resection: a Physical Trigger For Transcriptional Simentioning
confidence: 67%
See 1 more Smart Citation
“…This conclusion highlights the differences between different biological systems since DDR kinases ATM and ATR are dispensable for transcriptional repression in yeast , while they play key roles in mammals, as described above. Several observations seem to exclude a key role for resection in DSB‐dependent transcriptional silencing in mammals.…”
Section: Dna‐end Resection: a Physical Trigger For Transcriptional Simentioning
confidence: 67%
“…More recently, Manfrini et al . extended this observation by showing that such decrease was not restricted to the MAT locus: DSBs at three distinct sites reduced both the steady‐state RNA levels of genes flanking the breaks and RNAPII occupancy, in a manner inversely proportional to the distance from the break. Of note, when resection was impaired by inactivating the key nucleases MRX (Mre11‐Rad50‐Xrs2) complex and the exonuclease 1 (Exo1), both transcription and RNAPII binding were restored to an extent depending on the severity of the resection defect.…”
Section: Dna‐end Resection: a Physical Trigger For Transcriptional Simentioning
confidence: 78%
“…Thus, AddAB-dependent processing of DSB ends could affect the transcription of genes flanking a break site, as shown recently in yeast [54]. To test this possibility in Caulobacter , we performed RNA-seq on swarmer cells subjected to a single DSB.…”
Section: Resultsmentioning
confidence: 95%
“…Because fork progression is reduced at both DAFCs, collapsed forks and unrepaired DSBs likely accumulate 5-10 kb from the chorion genes. Several studies have found that DSB generation leads to a decrease in local transcription, and a recent study in yeast found that a single unrepaired DSB reduces transcription up to 10 kb away on either side of the break site (31). We therefore propose that the absence of MMEJ repair leads to an accumulation of DSBs, inhibiting both fork progression and transcription at certain DAFCs.…”
Section: Discussionmentioning
confidence: 92%